Expiratory flow limitation and breathing strategies in overweight adolescents during submaximal exercise - Gibson, N.; Johnston, K.; Bear, N.; Stick, S.; Logie, K.; Hall, Graham (Nature Publishing Group, 2014)
Objective: To investigate whether ventilatory factors limit exercise in overweight and obese children during a 6-min step test and to compare ventilatory responses during this test with those of healthy weight children. Design: Cross-sectional, prospective comparative study. Subjects: Twenty-six overweight/obese subjects and 25 healthy weight subjects with no known respiratory illness. Measurements: Various fatness and fat distribution parameters (using air displacement plethysmography and anthropometry), pulmonary function tests, breath-by-breath gas analysis during exercise, perceived exertion. Results: Young people who are overweight or obese are more likely to experience expiratory flow limitation (expFL) during submaximal exercise compared with their healthy weight peers [OR 7.2 (1.4, 37.3), P=0.019]. Subjects who had lower lung volumes at rest were even more likely to experience exercise-induced expFLs [OR 8.35 (1.4–49.3)]. Both groups displayed similar breathing strategies during submaximal exercise. Conclusion: Young people who are overweight/obese are more likely to display expFL during submaximal exercise compared with children of healthy weight. Use of compensatory breathing strategies appeared to enable overweight children to avoid the experience of breathlessness at this intensity of exercise.